2017
DOI: 10.1007/s11011-017-0022-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hypericum scabrum extract on learning and memory and oxidant/antioxidant status in rats fed a long-term high-fat diet

Abstract: A high-fat diet (HFD) causes deficits in learning and memory by increasing oxidative stress. Antioxidants are known to improve learning and memory. Since Hypericum scabrum (H. scabrum) extract is rich in antioxidants, the aim of this study was to investigate the effects of the administration of H. scabrum extract on passive avoidance learning (PAL), novel object recognition (NOR), and locomotor activity in male rats on a HFD. Fifty-four male Wistar rats (weighing 220 ± 10 g) were divided into the following six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 96 publications
2
24
0
Order By: Relevance
“…It has been indicated that, its extract possess flavonoids, such as quercetin [70]; flavonoids act as antioxidants [71]. In confirmation of our results, administration of H. scabrum Ext in rats was shown to improve learning and memory and possess antioxidant activity [27]. In accordance with this finding, Pintana et al [72] have shown that an HFD impairs learning and memory, and treatment with garlic extract restores these impairments in obese insulinresistant rats.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…It has been indicated that, its extract possess flavonoids, such as quercetin [70]; flavonoids act as antioxidants [71]. In confirmation of our results, administration of H. scabrum Ext in rats was shown to improve learning and memory and possess antioxidant activity [27]. In accordance with this finding, Pintana et al [72] have shown that an HFD impairs learning and memory, and treatment with garlic extract restores these impairments in obese insulinresistant rats.…”
Section: Discussionsupporting
confidence: 89%
“…Fifty-four rats (weighing 220 ± 10 g) were divided into 6 groups (n = 9): (1) HFD group, given an HFD with 45% energy from fat; (2) HFD + Ext300 group, given an HFD supplemented with H. scabrum extract (300 mg/ kg); (3) HFD + Ext100 group, given an HFD supplemented with H. scabrum extract (100 mg/kg); (4) control group, given a normal diet with 10% energy from fat and received the saline through oral gavage once a day for 3 months; (5) H. scabrum 300 mg/kg (Ext300) group, given the standard diet supplemented with H. scabrum (300 mg/kg); (6) H. scabrum 100 mg/kg (Ext100) group, given the standard diet supplemented with H. scabrum (100 mg/kg). Rats received the extract through oral gavage once a day for 3 months [3,14,27]. The gavage was performed from 9:00 to 11:00 a.m. All experimental procedures were done under international standards of animal care approved by the Society for Neuroscience.…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…A subject rodent was located in the light chamber facing away from the guillotine door. After five seconds, the door was opened, and following the entrance of rat to the dark chamber, the door was closed, and an electrical shock (50-Hz square wave, one mA for 1.5 seconds) was induced (24)(25)(26). Afterward, 30 seconds later the animal was delivered to the cage.…”
Section: Passive Avoidance Trainingmentioning
confidence: 99%